KURIKULUM MERDEKA IN TWO SENIOR HIGH SCHOOLS: ITS IMPLEMENTATION IN EFL CLASSROOM - Kamal, Shofia (Universitas Indo Global Mandiri, 2023)
Components in the curriculum are altered and developed as the curriculum progresses. The developments are crucial aspects of the curriculum. Every change and progress that happens during the development of it should be investigated. Thus, there is a need for more research and literature that focus on the implementation of Kurikulum Merdeka and its impact on English Education in Indonesia. The lack of research about Kurikulum Merdeka happens because it is a new program that requires more studies and investigations. Therefore, this study aims to investigate the implementation of Kurikulum Merdeka in two different Senior High Schools, its impact on the teaching and learning English process, and a comparison of the implementation curriculum in the two schools. The research used qualitative research design. The Interview was the instrument used to gain the data in this research. The result found that the first school mixed the 2013 and Kurikulum Merdeka. The second school fully implemented and Profil Pelajar Pancasila. The difficulties of implementing it were related to English course time allocation and students’ different interests in learning English. This study implies that teachers can prepare themselves to avoid problems and difficulties found in this research by finding solutions and strategies when encountering similar difficulties during teaching and learning. Keywords: Kurikulum Merdeka, EFL classroom, impact, implementation, comparison